"Wounds of Regret": Critical Reflections on Competence, "Professional Intuition," and Informed Consent in Research with Intellectually Disabled People - Chelsea Temple Jones (Disability Studies Quarterly, 2021)
There is an increased interest in including people with intellectual disability labels in social science research. The ethical conundrums involved in doing so are far-reaching, and labelled people remain chronically excluded from knowledge production on the basis of medicalized conceptions of competence commonly espoused by research ethics boards (REB). Here, I critically reflect on my experience making strategic decisions about accessing a writing group made up of labelled adults for my doctoral research. I respond to Kate Holland's 2007 question: "whose interests are served by current ethics review standards and what do they exclude?" (p. 904) by juxtaposing current ethical standards of critical disability studies with my REB's concerns about three issues: prospective participants' competence; their cognitive abilities; and a lengthy recruitment timeline. My reflections on these issues speak to feelings of regret and resilience, and what it can mean to take lessons from engaging in institutional ethics in an unsatisfactory way. This account offers snapshots of decisions leading up to a research project, and the ways in which ethics review frameworks remain rooted in biomedical epistemological biases that serve outsider researchers and exclude labelled people from research about themselves.
Keywords: competence; relational ethics; institutional ethics; intellectual disability; informed consent